Tafsir Nusantara as the Epistemological Basis of Contextual Islam: Responding to Indonesian Challenges in the Global Era - Billah, M. Mu'tashim; Sulhadi, Asep (IAI BADRUS SHOLEH, 2025)
This paper examines Tafsir Nusantara—the Indonesian tradition of Qur’anic interpretation—as an epistemological foundation for contextual Islam in Indonesia’s plural society. Drawing upon both classical hermeneutical theory and local wisdom, this study argues that Tafsir Nusantara is not merely a cultural phenomenon but a dynamic intellectual paradigm capable of addressing modern issues such as pluralism, radicalism, and globalization. Through analytical comparison between traditional works like Tafsir al-Ibriz and modern commentaries such as Tafsir al-Mishbah, the paper explores how Indonesian scholars integrate universal Islamic values with indigenous ethics. It concludes that Tafsir Nusantara provides an inclusive and dialogical model of interpretation that strengthens Indonesia’s national identity while promoting moderate Islamic thought.